High- and low-field dielectric responses and ferroelectric properties of (Bi0.5Na0.5)Zr1-xTixO3ceramics - Panupong Jaiban (2018)
Bismuth sodium zirconate titanate (Bi 0.5 Na 0.5 )Zr 1-x Ti x O 3 with (x=0, 0.1, 0.2, 0.3, 0.4, 0.5 and 0.6) ceramics was fabricated by a conventional sintering technique at 850-1000 °C for 2 h. From X-ray diffraction study, three regions of different phases were observed in the ceramic sys tem; i.e., orthorhombic phase region (0≤x≤0.2), mixed-phase region (0.3≤x≤0.4), and rhombohedral phase region (0.5≤x≤0.6). It was observed that the phase evolution from orthorhombic to rhombohedral symmetry resulted in a noticeable increase of the dielectric properties. The results from the high- and low-field dielectric responses indicated that the dielectric properties of both BNZ and BNZT ceramics were dominantly attributed to the reversible contribution. It was also noticed that grain size showed only partial influence on the increase of low-field dielectric constant in Ti-rich BNZT ceramic. © 2012 Elsevier Ltd and Techna Group S.r.l.